EFEKTIVITAS PENDAYAGUNAAN ZAKAT PRODUKTIF BERDASARKAN ZAKAT CORE PRINCIPLES - Rohma, Mauliya; Pujiati, Tri (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
The phenomenon of zakat empowerment in Jombang, East Java, presents challenges that must be addressed to alleviate poverty. This study aims to assess the effectiveness of utilizing productive zakat funds based on the Zakat Core Principles at LAZNAS Yatim Mandiri Jombang. A descriptive qualitative method was employed in this research. Data were collected through field observations, semi-structured interviews, and documentation. The effectiveness of productive zakat funds was evaluated using the Allocation to Collection Ratio (ACR) and the speed of zakat distribution. The findings reveal that the average distribution of zakat funds for the mustahik economic empowerment program from 2019 to 2023 falls under the Fairly Effective category, at approximately 50%. Additionally, the distribution speed for the five mustahik economic empowerment programs at LAZNAS Yatim Mandiri Jombang is categorized as fast and efficient. This study concludes that LAZNAS Yatim Mandiri Jombang has well-defined and appropriate mustahik targets, ensuring that productive zakat funds are effectively allocated. The findings highlight the potential of zakat as an optimal tool for poverty alleviation and social empowerment.